Digital Identity - Majeed Mohamed Fareed Majeed; Abdurahman Adisaputera; Muhammad Ridwan (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2020)
With the penetration and spread of the Internet in our daily life, issues related to our identity on the Internet and their potential impacts on our lives, whether positive or negative, have become very important. We, as individuals, interact with a number of websites and services on the Internet that require an account (username and password) to access. These sites range from simple news sites that limit the number of articles that you can read anonymously in a certain period of time, to financial services or healthcare sites or others. Similar services on the Internet require that you know with certainty that you are definitely "you" before granting you access to any private information. Of course, we want them to confirm our identity before allowing access to this type of very sensitive information, which can be used to inflict harm. Take us in different ways if you fall into the wrong hands. The presence in the virtual world has formed the digital identity, and this digital identity has different effects on the morals and habits of the users in this virtual world. Because of the existence of a digital identity, you may also be exposed to some type of privacy crime. In this case, we must study and adapt to create patterns of coexistence and resilience in the digital environment.